The Role of Trust in the Satisfaction of Civil Servants Receiving Promotion Services in Kendal Regency - Romadhona, Jesa Arinda; Wardoyo, Paulus; Utaminingsih, Adijati (Universitas Pamulang, 2024)
The service satisfaction is an indicator of success in the public services. An organization that is oriented toward public services such as human resources agency, education and training in district kendal has an important role in focusing all the activities to increase service satisfaction in the field of human resources included the promotion of civil servant service. But, based on a survey in 2022 and 2023, the responder's satisfaction fell down. This study aims to analyze the influence of service quality to the service satisfaction promotion, analyzing the influence of innovation to the service satisfaction promotion, analyzing the influence of employee's performance to the service satisfaction promotion, analyzing the ability of trust in moderating influence of service quality to the service satisfaction, analyzing the ability of trust in moderating influence of innovation to the service satisfaction, analyzing the ability of trust in moderating influence of employee's performance to the service satisfaction. The data analysis technique uses Moderated Regression Analysis through reliability, and hypothesis testing. The result showed that service quality affects service satisfaction. Innovation affects service satisfaction, employee's performance affects service satisfaction. Trust can mediate the relationship between service quality and service satisfaction. Trust can not mediate the relationship between innovation and service satisfaction. Trust is unable to mediate the relationship between employee's performance and service satisfaction. The research implication are expected to help in the development of human resource management theory by providing empirical evidence of how role of trust in increasing service satisfaction. The contribution of this research is that Agency of Employee, Education and Training can use the results of this study to develop more effective managerial strategies to improve service satisfaction through service quality, innovation, employee's performance, and trust of service.